A New Paradigm For Sustainable Minerals Extraction - P. Somasundaran (International Mineral Processing Congress, 2012)
While sustainability itself needs to be redefined in a selfless way, methods of measuring and optimizing it also need to be reformulated. Gone are the days when we had the luxury of abundant resources and the freedom to extract values in self-centered ways. In the past, focus has been mostly on reagent performance, processing operations, and upgrading of tools to maximize rather than optimize value extraction from the earth's crust. Today we as extractors face a new set of challenges that include value separation from low quality resources including wastes, but within the energy, environment, and societal constraints. Development of such technology depends on understanding the role of entities and concepts such as bio-molecular interactions at surfaces, forces involved in inter-granular versus intra-granular fracture in new fragmentation methods, robotic in-situ or extraterrestrial mining, exploiting new membrane and nano technology, use of new sensors and actuators for detection and separation and computation capabilities for faster and economical processing. Equally importantly, we need to communicate with everyone what we foresee and anticipate when we extrapolate the type-performance-cost relationship of ores to the era ahead of us and establish viable schemes for ecological survival. Keywords: sustainable mineral extraction